Speech Abnormalities and Temporal Lobe Seizures - J Gordon Millichap (Pediatric Neurology Briefs)
The role of speech manifestations in the lateralization of temporal lobe seizures was reviewed at the Section of Epilepsy and Clinical Neurophysiology, Department of Neurology, Cleveland Clinic Foundation, Cleveland, OH by the review of videotapes of 100 complex seizures in 35 patients who underwent temporal lobectomy for intractable epilepsy.